Nurses' and midwives' views on male partner involvement in maternity care in Imo, Nigeria (2021)
Background/Aims: In 2015, the World Health Organization recommended male partner involvement in maternal and child health as an effective strategy to combat maternal and child health in pregnancy. Healthcare practitioners' acceptance of male partners in maternal and child healthcare is likely to improve provider and patient satisfaction. The main objective of the study was to assess nurses' and midwives' perceptions of male partner involvement in maternity care, and their willingness and constraints to performing it in selected hospitals in Imo, Nigeria. Methods: A mixed-method approach was used to gather data from nurses and midwives in the antenatal care, labour and postnatal care wards of selected hospitals. A semi-structured questionnaire and interview guide were used to collect data assessing the participants' perceptions of male partner involvement in maternity care and of the barriers to it. Quantitative data were analysed through bivariate analysis, using the Chi squared test, and key quotes were extracted from qualitative data to illustrate relevant points. Results: The majority (57%) of the respondent had a good perception of the concept of male partner involvement. The ward that a participant worked in significantly affected their perception (P=0.01). Respondents were willing to accept male partners in maternity care through education and providing more male-friendly services. However, sociocultural, hospital policy and structural factors restricted acceptance of men in the wards. Conclusions: Nurses and midwives in all wards should be educated on the importance of male partner involvement in maternity care. Nurses and midwives need to engage in community health education programmes that will modify cultural constraints to male partner involvement and facilities should modify their structure and policies to be more male-friendly.